Cost-effectiveness of the dual prevention pill for contraception and HIV pre-exposure prophylaxis - Milali, Masabho P.; Resar, Danielle; Kaftan, David; Campbell, Jennifer; Olowu, Adebanjo; Edwards, Danny; Platais, Ingrida; Kim, Hae-Young; Jenkins, Sarah; Bershteyn, Anna (Frontiers in Reproductive Health, 2023)
Introduction: Women in sub-Saharan Africa (SSA) experience the world’s highest rates of both HIV infection and unintended pregnancy. The Dual Prevention Pill (DPP) is a novel multipurpose prevention technology (MPT) that co-formulates HIV pre-exposure prophylaxis (PrEP) and combined hormonal oral contraception into a single daily pill. The DPP may be preferred by women with dual needs. However, most SSA countries face severe healthcare resource constraints. Research is needed to assess whether, in what populations, and in what use cases the DPP would be cost-effective. Methods: We augmented an agent-based SSA HIV model with maternal health parameters including unintended pregnancy, abortion, and maternal mortality. Based on a previous market analysis, we assumed a primary DPP user population of current oral contraceptive users ages 25-49, and alternative user populations in different risk groups (age 15-24, sex workers, HIV-serodiscordant couples) and baseline product use profiles (unmet need for contraception, oral PrEP use, condom use). In three geographies (western Kenya, Zimbabwe, South Africa), we estimated HIV infections averted, pregnancies averted, disability-adjusted life-years (DALYs) averted, and the incremental cost-effectiveness ratio (ICER) over a 30-year time horizon, assuming equivalent adherence to the DPP as to oral contraceptives, higher adherence, or lower adherence. Results: The DPP is likely to be cost-effective in current oral PrEP users with high adherence (>73%) and cost-saving in PrEP users with low adherence (30%). It is also likely to be cost-saving in sex workers and serodiscordant couples not on PrEP, both for unmet need for contraception or current oral contraception users. DPP is unlikely to be cost-effective in oral contraceptive users ages 25-49 and could be net harmful, depending on the setting, if it substantially reduced contraceptive adherence. Results were robust to a range of time horizons or discount rates. Conclusion: The DPP has the potential to be cost-effective and cost-saving in populations at substantial HIV risk. Outcomes are sensitive to adherence, implying that effective counseling and decision-making tools for users considering the DPP will be essential. More research is needed to understand real-life adherence patterns and ensure health benefits achieved from contraception alone are not lost.